Composite high-temperature piezoelectric ceramic material and preparation method thereof

By doping composite high-priced ions, adding WO3 and ZnSO4, and adding functional fillers during powder ball milling, the crystal structure and sintering performance of BNT-based piezoelectric ceramics are optimized, and its piezoelectric performance is low and its temperature stability is poor. The problem of high-voltage electrical activity and mechanical properties have been improved.

CN119462132AActive Publication Date: 2025-02-18DEZHOU INKANA INSTR CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510057242.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-02-18
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The piezoelectric ceramic materials have low piezoelectric properties, poor temperature stability and low dielectric constant, making them difficult to effectively apply in some fields.

Method used

Using the chemical formula of Bi0.5-x[Mn0.25Sn0.5Pr0.25]xNa0.5TiO3+a%WO3+b%ZnSO4, the high-valent ions are doped and the addition of WO3 and ZnSO4 are added, and during the powder ball milling process Add functional fillers to control the preparation process and parameters, and optimize the crystal structure and sintering performance of the ceramic.

Benefits of technology

The piezoelectric activity, Curie temperature, dielectric constant and mechanical properties of ceramics are significantly improved, and their electrical and mechanical properties are enhanced in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of piezoelectric ceramic materials, and particularly discloses a composite high-temperature piezoelectric ceramic material and a preparation method thereof, the chemical general formula of the composite high-temperature piezoelectric ceramic material is Bi < 0.5-x > [Mn < 0.25 > Sn < 0.5 > Pr < 0.25 >] < x > Na < 0.5 > TiO < 3 + a >% WO < 3 + b >% ZnSO4, the components and proportion of the base material are adjusted and optimized, meanwhile, WO3 and ZnSO4 with specific content are adopted as additives, the piezoelectric activity and thermal stability of the piezoelectric ceramic can be improved, functional filler is added in the preparation process, sintering efficiency is improved, the ceramic material forms a more compact crystal structure, and the piezoelectric ceramic has a good application prospect. The strength and the toughness of the ceramic material are enhanced. The composite high-temperature piezoelectric ceramic material has high Curie temperature and high piezoelectric activity, and the application range of the piezoelectric ceramic material can be effectively widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of piezoelectric ceramic materials, and more specifically, to a composite high-temperature piezoelectric ceramic material and a preparation method thereof. Background Art

[0002] Piezoelectric ceramics are information functional ceramic materials that can convert mechanical energy and electrical energy into each other. In addition to piezoelectricity, piezoelectric ceramics also have dielectric properties and elasticity, and have been widely used in medical imaging, acoustic sensors, acoustic transducers, ultrasonic motors and other fields. At present, lead-based piezoelectric ceramics dominate the market, such as PZT, PMN, PZN, etc. These ceramics have excellent piezoelectric properties, but the lead element can cause great harm to the environment and human body. Therefore, lead-free piezoelectric ceramics replacing lead-containing piezoelectric ceramics has become a hot spot in material research. Bismuth sodium titanate (BNT)-based piezoelectric ceramics, as a perovskite-type ferroelectric with composite substitution of A-site ions, are considered to be one of the most promising lead-free material systems. BNT-based lead-free piezoelectric ceramics have excellent ferroelectric properties and a high Curie temperature, but their piezoelectric properties are still lower than those of traditional lead-based piezoelectric ceramics, and their temperature stability is poor. They are prone to cracking during high-temperature polarization and are difficult to sinter into a dense structure. At the same time, BNT-based ceramics have a low dielectric constant and a large coercive electric field. These shortcomings limit the application of BNT-based lead-free piezoelectric ceramics in certain fields. Therefore, the present application proposes a composite high-temperature piezoelectric ceramic material and a preparation method thereof, which not only has a high Curie temperature, but also has high voltage electrical activity and excellent mechanical properties. Summary of the invention

[0003] In order to solve the problems of low piezoelectric performance, poor temperature stability and low dielectric constant of bismuth sodium titanate (BNT) based piezoelectric ceramics, the present application provides a composite high-temperature piezoelectric ceramic material and a preparation method thereof.

[0004] In the first aspect, the present application provides a composite high-temperature piezoelectric ceramic material, which adopts the following technical solution: A composite high temperature piezoelectric ceramic material, the chemical formula of which is as follows: Bi 0.5-x [Mn 0.25 Sn 0.5 Pr 0.25 ] x Na 0.5 TiO3+a%WO3+b%ZnSO4; where x=0.1-0.3, a=1-3, b=0.4-0.6, WO3 accounts for Bi 0.5-x [Mn 0.25 Sn 0.5 Pr 0.25 ] x Na 0.5TiO3 accounts for 1%-3% of the total molar amount, ZnSO4 accounts for Bi 0.5-x [Mn 0.25 Sn 0.5 Pr 0.25 ] x Na 0.5 0.4%-0.6% of the total molar amount of TiO3.

[0005] In a second aspect, the present application provides a method for preparing a composite high-temperature piezoelectric ceramic material, which specifically comprises the following steps: S1. According to the chemical formula, weigh Bi2O3 powder, MnO2 powder, SnO2 powder, Pr6O 11 powder, Na2CO3 powder, TiO2 powder, WO3 powder and ZnSO4 powder; S2, Bi2O3 powder, MnO2 powder, SnO2 powder, Pr6O 11 The powder, Na2CO3 powder, TiO2 powder and ethanol solution are mixed, ball-milled and dried, and then pre-calcined at 850-870°C for 3-5h to obtain a powder; S3, adding WO3 powder, ZnSO4 powder and functional filler to the powder, drying after ball milling, adding auxiliary agent for granulation, sieving and molding to obtain a ceramic body; S4. Debinding the ceramic body at 600-800° C., and then sintering at 1000-1200° C. for 2-4 hours to obtain a composite high-temperature piezoelectric ceramic material.

[0006] Preferably, the amount of ethanol solution added in step S2 is 10-14 times the mass of Bi2O3 powder.

[0007] Preferably, the mass concentration of the ethanol solution in step S2 is 60%-80%.

[0008] Preferably, in step S2, the ball milling speed is 240-260 r / min, the ball milling time is 24-36 h, and the drying temperature is 70-90° C.

[0009] Preferably, the amount of the functional filler added in step S3 is 4%-8% of the mass of the powder.

[0010] Preferably, the functional filler is prepared by the following method: (1) mixing natural gum with water, adding sodium hydroxide, and stirring to obtain a natural gum solution; (2) adding lauryl amidopropyl betaine, polyethylene glycol and water to the composite filler, stirring and mixing to obtain a modified filler; (3) Adding the modified filler into the natural gum solution, stirring and mixing, ball milling, and drying to obtain the functional filler.

[0011] Preferably, the natural gum in step (1) is at least one of gum arabic, peach gum and balsam pear gum.

[0012] Preferably, the natural gum in step (1) is composed of a mixture of gum arabic and gum salsa in a mass ratio of 5-7:1-3.

[0013] Preferably, in step (1), the mass ratio of natural gum, water and sodium hydroxide is 10-12:50:1-3.

[0014] Preferably, the composite filler in step (2) is composed of niobium nitride, silicon dioxide and calcium carbonate mixed in a mass ratio of 6-8:1-3:2.

[0015] Preferably, in step (2), the mass ratio of the composite filler, laurylamidopropyl betaine, polyethylene glycol and water is 6-10:1-3:2-4:50.

[0016] Preferably, in step (3), the mass ratio of the modified filler to the natural gum solution is 10-18:50.

[0017] Preferably, in step (3), the ball milling speed is 100-140 r / min, the ball milling time is 3-5 h, and the drying temperature is 60-80°C.

[0018] Preferably, in step S3, the ball milling speed is 200-220 r / min, the ball milling time is 18-30 h, and the drying temperature is 80-100° C.

[0019] Preferably, the auxiliary agent in step S3 is a PVA solution with a mass fraction of 4%-6%.

[0020] In summary, this application has the following beneficial effects: 1. The present application provides a composite high-temperature piezoelectric ceramic material, which uses the raw materials of traditional BNT-based lead-free piezoelectric ceramics as the base material and uses composite high-valent ions [Mn 0.25 Sn 0.5 Pr 0.25 ] 4.75+ Doping with Bi to replace the A position 3+ ions, and doped with WO3 and ZnSO4, functional fillers were added during the powder ball milling process, and the prepared piezoelectric ceramic material had high piezoelectric activity and high Curie temperature by controlling the preparation process and parameters.

[0021] 2. This application uses composite high-valent ions [Mn 0.25 Sn 0.5 Pr 0.25 ] 4.75+ Doping with Bi to replace the A position3+ Ions can cause lattice distortion of piezoelectric ceramics, optimize the crystal structure of piezoelectric ceramics, make the crystal structure more dense and uniform, and improve the piezoelectric constant, dielectric constant and electromechanical coupling coefficient of ceramics without reducing the Curie temperature, thereby improving the piezoelectric activity of piezoelectric ceramics; the doping of Mn, Sn and Pr can also improve the thermal stability of piezoelectric ceramics, so that the ceramics can maintain good electrical and mechanical properties even in high temperature environments. Doping WO3 can significantly improve the dielectric constant of piezoelectric ceramics, and can improve the density and strength of ceramics, making them more resistant to high temperature and wear. Doping ZnSO4 can promote the growth and development of crystals inside piezoelectric ceramics, making the crystal structure more dense and uniform, and at the same time can reduce the sintering temperature of ceramics. The two can synergistically enhance the piezoelectric activity and density of piezoelectric ceramics.

[0022] 3. In the present application, a functional filler is added during the ball milling process of the raw material powder. The functional filler is prepared by first modifying the composite filler with lauryl amide propyl betaine and polyethylene glycol, and then uniformly coating the surface of the composite filler particles with a natural gum solution. Niobium nitride, silicon dioxide and calcium carbonate are compounded to form a composite filler. During the sintering process, niobium nitride can serve as a hard phase to significantly improve the hardness and wear resistance of the ceramic. Silicon dioxide can form a stable silicate liquid phase at high temperature, which can promote sintering, reduce the sintering temperature, refine the grains, and make the ceramics denser and more uniform. Calcium carbonate can decompose at high temperature to produce calcium oxide and other oxides that can react with other components in the ceramic to form a high-temperature glass phase, thereby promoting sintering. The three complement each other and can synergistically enhance the sintering performance and mechanical properties of ceramic materials. Modification with lauryl amide propyl betaine and polyethylene glycol can improve the wettability and dispersibility of the composite filler and enhance the interaction with the raw material powder. The modified composite filler is then coated with a natural gum solution to form a stable protective layer, which improves the stability and uniformity of the composite filler and thus improves the sintering efficiency. The encapsulation of the natural gum solution can also prevent the abnormal growth of ceramic grains, thereby forming a denser crystal structure and enhancing the strength and toughness of the ceramic material. DETAILED DESCRIPTION

[0023] The present application is further described in detail below with reference to the embodiments.

[0024] The Bi2O3 powder (effective ingredient content: 99.99%, purchased from Dinghong (Shanghai) New Material Technology Co., Ltd.), MnO2 powder (CAS No.: 1313-1319, purchased from Leiyang Xingfa Manganese Industry Co., Ltd.), SnO2 powder (CAS No.: 18282-10-5, purchased from Zhangjiakou Yuzheng Powder Material Co., Ltd.), Pr6O 11Powder (Item No.: DS20220316, purchased from Shandong Desheng New Materials Co., Ltd.), Na2CO3 powder (CAS No.: 497-19-8, purchased from Hubei Xinghengye Technology Co., Ltd.), TiO2 powder (Specification: 30μm, purchased from Lingke Element (Beijing) Technology Co., Ltd.), WO3 powder (CAS No.: 1314-35-8, purchased from Qinghe Chaotai Metal Materials Co., Ltd.), ZnSO4 powder (CAS No.: 7733-02-0, purchased from Tianjin Jinhui Taiya Chemical Reagent Co., Ltd.), gum arabic (Model: DL-GH, purchased from Tai'an Dingli Glue Co., Ltd.), duck soap Gum (purity: >98%, purchased from Xi'an Kangnuo Chemical Co., Ltd.), lauryl amidopropyl betaine (CAS No.: 4292-10-8, purchased from Hubei Xinhongli Chemical Co., Ltd.), polyethylene glycol (CAS No.: 25322-68-3, purchased from Liaoning Kelong Fine Chemical Co., Ltd.), niobium nitride (CAS No.: 24621-21-4, purchased from Hubei Jusheng Technology Co., Ltd.), silicon dioxide (CAS No.: 14808-60-7, purchased from Wuhan Jixin Yibang Biotechnology Co., Ltd.), and calcium carbonate (CAS No.: 471-34-1, purchased from Shandong Yonglida New Materials Technology Co., Ltd.).

[0025] Example 1 A composite high temperature piezoelectric ceramic material, the general chemical formula of which is: Bi 0.4 [Mn 0.25 Sn 0.5 Pr 0.25 ] 0.1 Na 0.5 TiO3+1%WO3+0.4%ZnSO4; among them, WO3 accounts for Bi 0.4 [Mn 0.25 Sn 0.5 Pr 0.25 ] 0.1 Na 0.5 TiO3 accounts for 1% of the total molar amount, ZnSO4 accounts for Bi 0.4 [Mn 0.25 Sn 0.5 Pr 0.25 ] 0.1 Na 0.5 0.4% of the total molar amount of TiO3.

[0026] A method for preparing a composite high-temperature piezoelectric ceramic material comprises the following specific steps: S1. According to the chemical formula, weigh Bi2O3 powder, MnO2 powder, SnO2 powder, Pr6O 11 powder, Na2CO3 powder, TiO2 powder, WO3 powder and ZnSO4 powder; S2, Bi2O3 powder, MnO2 powder, SnO2 powder, Pr6O 11 The powder, Na2CO3 powder, TiO2 powder and 60% ethanol solution (the amount used is 10 times the mass of Bi2O3 powder) are stirred and mixed at a speed of 400r / min for 20min, ball-milled at a speed of 240r / min for 24h, dried at 70℃ for 1h, and then pre-calcined at 850℃ for 3h to obtain powder; S3, add WO3 powder, ZnSO4 powder and functional filler (the amount is 4% of the mass of the powder) to the powder, ball mill at a speed of 200r / min for 18h, dry at 80℃ for 1h, then add 4% PVA solution by mass to granulate, pass through a 100-mesh sieve, and press at a pressure of 60MPa to obtain a ceramic body; S4. Debinding the ceramic body at 600° C., and then sintering at 1000° C. for 2 h to obtain a composite high-temperature piezoelectric ceramic material.

[0027] Wherein, the functional filler in step S3 is prepared by the following method: (1) Mixing natural gum (composed of gum arabic and gum balsam pear mixed in a mass ratio of 5:1) with water in a mass ratio of natural gum, water and sodium hydroxide of 10:50:1, adding sodium hydroxide, stirring and mixing at a speed of 600 r / min for 10 minutes, and obtaining a natural gum solution; (2) According to the mass ratio of composite filler, lauryl amidopropyl betaine, polyethylene glycol and water being 6:1:2:50, a composite filler (composed of niobium nitride, silicon dioxide and calcium carbonate mixed in a mass ratio of 6:1:2) is added to lauryl amidopropyl betaine, polyethylene glycol and water, and the mixture is stirred and mixed at a speed of 600 r / min for 10 min to obtain a modified filler; (3) The modified filler was added to the natural gum solution at a mass ratio of 10:50, and the mixture was stirred at 400 r / min for 20 min. The mixture was then ball-milled at 100 r / min for 3 h, and dried at 60 °C for 1 h to obtain the functional filler.

[0028] Example 2 A composite high temperature piezoelectric ceramic material, the general chemical formula of which is: Bi 0.35 [Mn 0.25 Sn 0.5 Pr 0.25 ] 0.15 Na 0.5 TiO3+1.5%WO3+0.45%ZnSO4; among them, WO3 accounts for Bi 0.35 [Mn 0.25 Sn 0.5 Pr 0.25 ]0.15 Na 0.5 TiO3 accounts for 1.5% of the total molar amount, ZnSO4 accounts for Bi 0.35 [Mn 0.25 Sn 0.5 Pr 0.25 ] 0.15 Na 0.5 0.45% of the total molar amount of TiO3.

[0029] A method for preparing a composite high-temperature piezoelectric ceramic material comprises the following specific steps: S1. According to the chemical formula, weigh Bi2O3 powder, MnO2 powder, SnO2 powder, Pr6O 11 powder, Na2CO3 powder, TiO2 powder, WO3 powder and ZnSO4 powder; S2, Bi2O3 powder, MnO2 powder, SnO2 powder, Pr6O 11 The powder, Na2CO3 powder, TiO2 powder and 65% ethanol solution (the amount used is 11 times the mass of Bi2O3 powder) are stirred and mixed at a speed of 450r / min for 25min, ball-milled at a speed of 245r / min for 27h, dried at 75℃ for 1.5h, and then pre-calcined at 855℃ for 3.5h to obtain powder; S3, add WO3 powder, ZnSO4 powder and functional filler (the amount is 5% of the mass of the powder) to the powder, ball mill at a speed of 205r / min for 21h, dry at 85℃ for 1.5h, then add 4.5% PVA solution by mass to granulate, pass through a 105 mesh sieve, and press under a pressure of 65MPa to obtain a ceramic body; S4. Debinding the ceramic body at 650° C., and then sintering at 1050° C. for 2.5 h to obtain a composite high-temperature piezoelectric ceramic material.

[0030] Wherein, the functional filler in step S3 is prepared by the following method: (1) Mixing natural gum (composed of gum arabic and gum balsam pear in a mass ratio of 5.5:1.5) with water in a mass ratio of natural gum, water and sodium hydroxide of 10.5:50:1.5, adding sodium hydroxide, stirring and mixing at a speed of 650 r / min for 15 minutes, and obtaining a natural gum solution; (2) According to the mass ratio of composite filler, lauryl amidopropyl betaine, polyethylene glycol and water being 7:1.5:2.5:50, a composite filler (composed of niobium nitride, silicon dioxide and calcium carbonate mixed in a mass ratio of 6.5:1.5:2) was added to lauryl amidopropyl betaine, polyethylene glycol and water, and the mixture was stirred at a speed of 650 r / min for 15 min to obtain a modified filler; (3) The modified filler was added to the natural gum solution at a mass ratio of 12:50, and the mixture was stirred at 450 r / min for 25 min. The mixture was then ball milled at 110 r / min for 3.5 h, and dried at 65°C for 1.5 h to obtain the functional filler.

[0031] Example 3 A composite high temperature piezoelectric ceramic material, the general chemical formula of which is: Bi 0.3 [Mn 0.25 Sn 0.5 Pr 0.25 ] 0.2 Na 0.5 TiO3+2%WO3+0.5%ZnSO4; among them, WO3 accounts for Bi 0.3 [Mn 0.25 Sn 0.5 Pr 0.25 ] 0.2 Na 0.5 TiO3 accounts for 2% of the total molar amount, ZnSO4 accounts for Bi 0.3 [Mn 0.25 Sn 0.5 Pr 0.25 ] 0.2 Na 0.5 0.5% of the total molar amount of TiO3.

[0032] A method for preparing a composite high-temperature piezoelectric ceramic material comprises the following specific steps: S1. According to the chemical formula, weigh Bi2O3 powder, MnO2 powder, SnO2 powder, Pr6O 11 powder, Na2CO3 powder, TiO2 powder, WO3 powder and ZnSO4 powder; S2, Bi2O3 powder, MnO2 powder, SnO2 powder, Pr6O 11 The powder, Na2CO3 powder, TiO2 powder and 70% ethanol solution (the amount used is 12 times the mass of Bi2O3 powder) are stirred and mixed at a speed of 500 r / min for 30 min, ball-milled at a speed of 250 r / min for 30 h, dried at 80°C for 2 h, and then pre-calcined at 860°C for 4 h to obtain a powder; S3, add WO3 powder, ZnSO4 powder and functional filler (the amount is 6% of the mass of the powder) to the powder, ball mill at a speed of 210r / min for 24h, dry at 90℃ for 2h, then add 5% PVA solution by mass to granulate, pass through a 110-mesh sieve, and press under a pressure of 70MPa to obtain a ceramic body; S4. Debinding the ceramic body at 700° C., and then sintering at 1100° C. for 3 h to obtain a composite high-temperature piezoelectric ceramic material.

[0033] Wherein, the functional filler in step S3 is prepared by the following method: (1) Mixing natural gum (composed of gum arabic and gum balsam pear mixed in a mass ratio of 6:2) with water in a mass ratio of natural gum, water and sodium hydroxide of 11:50:2, adding sodium hydroxide, stirring and mixing at a speed of 700 r / min for 20 min, and obtaining a natural gum solution; (2) According to the mass ratio of composite filler, lauryl amidopropyl betaine, polyethylene glycol and water being 8:2:3:50, a composite filler (composed of niobium nitride, silicon dioxide and calcium carbonate mixed in a mass ratio of 7:2:2) is added to lauryl amidopropyl betaine, polyethylene glycol and water, and the mixture is stirred and mixed at a speed of 700 r / min for 20 min to obtain a modified filler; (3) The modified filler was added to the natural gum solution at a mass ratio of 14:50, and the mixture was stirred at 500 r / min for 30 min, then ball-milled at 120 r / min for 4 h, and dried at 70 °C for 2 h to obtain the functional filler.

[0034] Example 4 A composite high temperature piezoelectric ceramic material, the general chemical formula of which is: Bi 0.25 [Mn 0.25 Sn 0.5 Pr 0.25 ] 0.25 Na 0.5 TiO3+2.5%WO3+0.55%ZnSO4; among them, WO3 accounts for Bi 0.25 [Mn 0.25 Sn 0.5 Pr 0.25 ] 0.25 Na 0.5 TiO3 accounts for 2.5% of the total molar amount, ZnSO4 accounts for Bi 0.25 [Mn 0.25 Sn 0.5 Pr 0.25 ] 0.25 Na 0.5 0.55% of the total molar amount of TiO3.

[0035] A method for preparing a composite high-temperature piezoelectric ceramic material comprises the following specific steps: S1. According to the chemical formula, weigh Bi2O3 powder, MnO2 powder, SnO2 powder, Pr6O 11 powder, Na2CO3 powder, TiO2 powder, WO3 powder and ZnSO4 powder; S2, Bi2O3 powder, MnO2 powder, SnO2 powder, Pr6O 11 The powder, Na2CO3 powder, TiO2 powder and 75% ethanol solution (the amount used is 13 times the mass of Bi2O3 powder) are stirred and mixed at a speed of 550r / min for 35min, ball-milled at a speed of 255r / min for 33h, dried at 85℃ for 2.5h, and then pre-calcined at 865℃ for 4.5h to obtain powder; S3, add WO3 powder, ZnSO4 powder and functional filler (the amount is 7% of the mass of the powder) to the powder, ball mill at a speed of 215r / min for 27h, dry at 95℃ for 2.5h, then add 5.5% PVA solution by mass to granulate, pass through a 115 mesh sieve, and press at a pressure of 75MPa to obtain a ceramic body; S4. Debinding the ceramic body at 750° C., and then sintering at 1150° C. for 3.5 hours to obtain a composite high-temperature piezoelectric ceramic material.

[0036] Wherein, the functional filler in step S3 is prepared by the following method: (1) Mixing natural gum (composed of gum arabic and balsam pear gum in a mass ratio of 6.5:2.5) with water in a mass ratio of natural gum, water and sodium hydroxide of 11.5:50:2.5, adding sodium hydroxide, stirring and mixing at a speed of 750 r / min for 25 min, to obtain a natural gum solution; (2) According to the mass ratio of composite filler, lauryl amidopropyl betaine, polyethylene glycol and water being 9:2.5:3.5:50, a composite filler (composed of niobium nitride, silicon dioxide and calcium carbonate mixed in a mass ratio of 7.5:2.5:2) is added to lauryl amidopropyl betaine, polyethylene glycol and water, and the mixture is stirred at a speed of 750 r / min for 25 min to obtain a modified filler; (3) The modified filler was added to the natural gum solution at a mass ratio of 16:50, and the mixture was stirred at 550 r / min for 35 min. The mixture was then ball milled at 130 r / min for 4.5 h, and dried at 75°C for 2.5 h to obtain the functional filler.

[0037] Example 5 A composite high temperature piezoelectric ceramic material, the general chemical formula of which is: Bi 0.2 [Mn 0.25 Sn 0.5 Pr 0.25 ] 0.3 Na 0.5 TiO3+3%WO3+0.6%ZnSO4; among them, WO3 accounts for Bi 0.2 [Mn 0.25Sn 0.5 Pr 0.25 ] 0.3 Na 0.5 TiO3 accounts for 3% of the total molar amount, ZnSO4 accounts for Bi 0.2 [Mn 0.25 Sn 0.5 Pr 0.25 ] 0.3 Na 0.5 0.6% of the total molar amount of TiO3.

[0038] A method for preparing a composite high-temperature piezoelectric ceramic material comprises the following specific steps: S1. According to the chemical formula, weigh Bi2O3 powder, MnO2 powder, SnO2 powder, Pr6O 11 powder, Na2CO3 powder, TiO2 powder, WO3 powder and ZnSO4 powder; S2, Bi2O3 powder, MnO2 powder, SnO2 powder, Pr6O 11 The powder, Na2CO3 powder, TiO2 powder and 80% ethanol solution (the amount used is 14 times the mass of Bi2O3 powder) are stirred and mixed at a speed of 600 r / min for 40 min, ball-milled at a speed of 260 r / min for 36 h, dried at 90°C for 3 h, and then pre-calcined at 870°C for 5 h to obtain a powder; S3, add WO3 powder, ZnSO4 powder and functional filler (the amount is 8% of the mass of the powder) to the powder, ball mill at a speed of 220r / min for 30h, dry at 100℃ for 3h, then add 6% PVA solution by mass to granulate, pass through a 120-mesh sieve, and press under a pressure of 80MPa to obtain a ceramic body; S4. Debinding the ceramic body at 800° C., and then sintering at 1200° C. for 4 hours to obtain a composite high-temperature piezoelectric ceramic material.

[0039] Wherein, the functional filler in step S3 is prepared by the following method: (1) Mixing natural gum (composed of gum arabic and gum balsam pear mixed in a mass ratio of 7:3) with water in a mass ratio of natural gum, water and sodium hydroxide of 12:50:3, adding sodium hydroxide, stirring and mixing at a speed of 800 r / min for 30 minutes, and obtaining a natural gum solution; (2) According to the mass ratio of composite filler, lauryl amidopropyl betaine, polyethylene glycol and water being 10:3:4:50, a composite filler (composed of niobium nitride, silicon dioxide and calcium carbonate mixed in a mass ratio of 8:3:2) is added to lauryl amidopropyl betaine, polyethylene glycol and water, and the mixture is stirred and mixed at a speed of 800 r / min for 30 min to obtain a modified filler; (3) The modified filler was added to the natural gum solution at a mass ratio of 18:50, and the mixture was stirred at 600 r / min for 40 min, then ball-milled at 140 r / min for 5 h, and dried at 80 °C for 3 h to obtain the functional filler.

[0040] Comparative Example 1 Comparative Example 1 is the same as Example 1, except that there is no Pr in the composite high-valent ion. 3+ Ions, as follows: A composite high temperature piezoelectric ceramic material, the general chemical formula of which is: Bi 0.4 [Mn 1 / 3 Sn 2 / 3 ] 0.1 Na 0.5 TiO3+1%WO3+0.4%ZnSO4; among them, WO3 accounts for Bi 0.4 [Mn 1 / 3 Sn 2 / 3 ] 0.1 Na 0.5 TiO3 accounts for 1% of the total molar amount, ZnSO4 accounts for Bi 0.4 [Mn 1 / 3Sn 2 / 3 ] 0.1 Na 0.5 0.4% of the total molar amount of TiO3.

[0041] A method for preparing a composite high-temperature piezoelectric ceramic material comprises the following specific steps: S1. According to the stoichiometry of the chemical formula, weigh Bi2O3 powder, MnO2 powder, SnO2 powder, Na2CO3 powder, TiO2 powder, WO3 powder and ZnSO4 powder; S2, Bi2O3 powder, MnO2 powder, SnO2 powder, Na2CO3 powder, TiO2 powder and 60% ethanol solution (the amount is 10 times the mass of Bi2O3 powder) are stirred and mixed at a speed of 400r / min for 20min, ball milled at a speed of 240r / min for 24h, dried at 70℃ for 1h, and then pre-calcined at 850℃ for 3h to obtain powder; S3, add WO3 powder, ZnSO4 powder and functional filler (the amount is 4% of the mass of the powder) to the powder, ball mill at a speed of 200r / min for 18h, dry at 80℃ for 1h, then add 4% PVA solution by mass to granulate, pass through a 100-mesh sieve, and press at a pressure of 60MPa to obtain a ceramic body; S4. Debinding the ceramic body at 600° C., and then sintering at 1000° C. for 2 h to obtain a composite high-temperature piezoelectric ceramic material.

[0042] Comparative Example 2 Comparative Example 2 is the same as Example 1, except that there is no Sn in the composite high-valent ion. 4+ Ions, as follows: A composite high temperature piezoelectric ceramic material, the general chemical formula of which is: Bi 0.4 [Mn 0.5 Pr 0.5 ] 0.1 Na 0.5 TiO3+1%WO3+0.4%ZnSO4; among them, WO3 accounts for Bi 0.4 [Mn 0.5 Pr 0.5 ] 0.1 Na 0.5 TiO3 accounts for 1% of the total molar amount, ZnSO4 accounts for Bi 0.4 [Mn 0.5 Pr 0.5 ] 0.1 Na 0.5 0.4% of the total molar amount of TiO3.

[0043] A method for preparing a composite high-temperature piezoelectric ceramic material comprises the following specific steps: S1. According to the chemical formula, weigh Bi2O3 powder, MnO2 powder, Pr6O 11 powder, Na2CO3 powder, TiO2 powder, WO3 powder and ZnSO4 powder; S2, Bi2O3 powder, MnO2 powder, Pr6O 11 The powder, Na2CO3 powder, TiO2 powder and 60% ethanol solution (the amount used is 10 times the mass of Bi2O3 powder) are stirred and mixed at a speed of 400r / min for 20min, ball-milled at a speed of 240r / min for 24h, dried at 70℃ for 1h, and then pre-calcined at 850℃ for 3h to obtain powder; S3, add WO3 powder, ZnSO4 powder and functional filler (the amount is 4% of the mass of the powder) to the powder, ball mill at a speed of 200r / min for 18h, dry at 80℃ for 1h, then add 4% PVA solution by mass to granulate, pass through a 100-mesh sieve, and press at a pressure of 60MPa to obtain a ceramic body; S4. Debinding the ceramic body at 600° C., and then sintering at 1000° C. for 2 h to obtain a composite high-temperature piezoelectric ceramic material.

[0044] Comparative Example 3 Comparative Example 3 is the same as Example 1, except that there is no Mn in the composite high-valent ion. 6+ Ions, as follows: A composite high temperature piezoelectric ceramic material, the general chemical formula of which is: Bi 0.4 [Sn 2 / 3 Pr 1 / 3 ] 0.1 Na 0.5 TiO3+1%WO3+0.4%ZnSO4; among them, WO3 accounts for Bi 0.4 [Sn 2 / 3 Pr 1 / 3 ] 0.1 Na 0.5 TiO3 accounts for 1% of the total molar amount, ZnSO4 accounts for Bi 0.4 [Sn 2 / 3Pr 1 / 3 ] 0.1 Na 0.5 0.4% of the total molar amount of TiO3.

[0045] A method for preparing a composite high-temperature piezoelectric ceramic material comprises the following specific steps: S1. According to the chemical formula, weigh Bi2O3 powder, SnO2 powder, Pr6O 11 powder, Na2CO3 powder, TiO2 powder, WO3 powder and ZnSO4 powder; S2, Bi2O3 powder, SnO2 powder, Pr6O 11 The powder, Na2CO3 powder, TiO2 powder and 60% ethanol solution (the amount used is 10 times the mass of Bi2O3 powder) are stirred and mixed at a speed of 400r / min for 20min, ball-milled at a speed of 240r / min for 24h, dried at 70℃ for 1h, and then pre-calcined at 850℃ for 3h to obtain powder; S3, add WO3 powder, ZnSO4 powder and functional filler (the amount is 4% of the mass of the powder) to the powder, ball mill at a speed of 200r / min for 18h, dry at 80℃ for 1h, then add 4% PVA solution by mass to granulate, pass through a 100-mesh sieve, and press at a pressure of 60MPa to obtain a ceramic body; S4. Debinding the ceramic body at 600° C., and then sintering at 1000° C. for 2 h to obtain a composite high-temperature piezoelectric ceramic material.

[0046] Comparative Example 4 Comparative Example 4 is the same as Example 1, except that ZnSO4 is used instead of WO3, as follows: A composite high temperature piezoelectric ceramic material, the general chemical formula of which is: Bi 0.4 [Mn 0.25 Sn 0.5 Pr 0.25 ] 0.1 Na0.5 TiO3+1.4%ZnSO4; among them, ZnSO4 accounts for Bi 0.4 [Mn 0.25 Sn 0.5 Pr 0.25 ] 0.1 Na 0.5 1.4% of the total molar amount of TiO3.

[0047] A method for preparing a composite high-temperature piezoelectric ceramic material comprises the following specific steps: S1. According to the chemical formula, weigh Bi2O3 powder, MnO2 powder, SnO2 powder, Pr6O 11 powder, Na2CO3 powder, TiO2 powder and ZnSO4 powder; S2, Bi2O3 powder, MnO2 powder, SnO2 powder, Pr6O 11 The powder, Na2CO3 powder, TiO2 powder and 60% ethanol solution (the amount used is 10 times the mass of Bi2O3 powder) are stirred and mixed at a speed of 400r / min for 20min, ball-milled at a speed of 240r / min for 24h, dried at 70℃ for 1h, and then pre-calcined at 850℃ for 3h to obtain powder; S3, adding ZnSO4 powder and functional filler (the amount is 4% of the mass of the powder) to the powder, ball milling at a speed of 200r / min for 18h, drying at 80°C for 1h, and then adding 4% PVA solution by mass to granulate, passing through a 100-mesh sieve, and pressing at a pressure of 60MPa to obtain a ceramic body; S4. Debinding the ceramic body at 600° C., and then sintering at 1000° C. for 2 h to obtain a composite high-temperature piezoelectric ceramic material.

[0048] Comparative Example 5 Comparative Example 5 is the same as Example 1, except that WO3 is used instead of ZnSO4, as follows: A composite high temperature piezoelectric ceramic material, the general chemical formula of which is: Bi 0.4 [Mn 0.25 Sn 0.5 Pr 0.25 ] 0.1 Na 0.5 TiO3+1.4%WO3; among them, WO3 accounts for Bi 0.4 [Mn 0.25 Sn 0.5 Pr 0.25 ] 0.1 Na 0.5 1.4% of the total molar amount of TiO3.

[0049] A method for preparing a composite high-temperature piezoelectric ceramic material comprises the following specific steps: S1. According to the chemical formula, weigh Bi2O3 powder, MnO2 powder, SnO2 powder, Pr6O 11 powder, Na2CO3 powder, TiO2 powder and WO3 powder; S2, Bi2O3 powder, MnO2 powder, SnO2 powder, Pr6O 11 The powder, Na2CO3 powder, TiO2 powder and 60% ethanol solution (the amount used is 10 times the mass of Bi2O3 powder) are stirred and mixed at a speed of 400r / min for 20min, ball-milled at a speed of 240r / min for 24h, dried at 70℃ for 1h, and then pre-calcined at 850℃ for 3h to obtain powder; S3, add WO3 powder and functional filler (the amount is 4% of the mass of the powder) to the powder, ball mill at a speed of 200r / min for 18h, dry at 80℃ for 1h, then add 4% PVA solution by mass to granulate, pass through a 100-mesh sieve, and press under a pressure of 60MPa to obtain a ceramic body; S4. Debinding the ceramic body at 600° C., and then sintering at 1000° C. for 2 h to obtain a composite high-temperature piezoelectric ceramic material.

[0050] Comparative Example 6 Comparative Example 6 is the same as Example 1, except that only gum arabic is used as the natural gum, specifically as follows: Wherein, the functional filler in step S3 is prepared by the following method: (1) Gum arabic and water are mixed in a mass ratio of 10:50:1, sodium hydroxide is added, and the mixture is stirred at a speed of 600 r / min for 10 min to obtain a gum arabic solution; (2) According to the mass ratio of composite filler, lauryl amidopropyl betaine, polyethylene glycol and water being 6:1:2:50, a composite filler (composed of niobium nitride, silicon dioxide and calcium carbonate mixed in a mass ratio of 6:1:2) is added to lauryl amidopropyl betaine, polyethylene glycol and water, and the mixture is stirred and mixed at a speed of 600 r / min for 10 min to obtain a modified filler; (3) The modified filler was added to the gum arabic solution at a mass ratio of 10:50, and the mixture was stirred at 400 r / min for 20 min. The mixture was then ball-milled at 100 r / min for 3 h, and dried at 60 °C for 1 h to obtain the functional filler.

[0051] Comparative Example 7 Comparative Example 7 is the same as Example 1, except that the natural gum is only selected from the gum of the duck soap tree, as follows: Wherein, the functional filler in step S3 is prepared by the following method: (1) Mixing the balsam pear gum and water in a mass ratio of balsam pear gum, water and sodium hydroxide of 10:50:1, adding sodium hydroxide, and stirring the mixture at a speed of 600 r / min for 10 min to obtain a balsam pear gum solution; (2) According to the mass ratio of composite filler, lauryl amidopropyl betaine, polyethylene glycol and water being 6:1:2:50, a composite filler (composed of niobium nitride, silicon dioxide and calcium carbonate mixed in a mass ratio of 6:1:2) is added to lauryl amidopropyl betaine, polyethylene glycol and water, and the mixture is stirred and mixed at a speed of 600 r / min for 10 min to obtain a modified filler; (3) The modified filler was added to the balsam pear gum solution at a mass ratio of 10:50, and the mixture was stirred at 400 r / min for 20 min, then ball-milled at 100 r / min for 3 h, and dried at 60°C for 1 h to obtain the functional filler.

[0052] Comparative Example 8 Comparative Example 8 is the same as Example 1, except that the modified filler is not wrapped with the natural gum solution, as follows: Wherein, the functional filler in step S3 is prepared by the following method: (1) According to the mass ratio of composite filler, lauryl amidopropyl betaine, polyethylene glycol and water being 6:1:2:50, a composite filler (composed of niobium nitride, silicon dioxide and calcium carbonate mixed in a mass ratio of 6:1:2) is added to lauryl amidopropyl betaine, polyethylene glycol and water, and the mixture is stirred and mixed at a speed of 600 r / min for 10 minutes to obtain a modified filler; (2) The modified filler was ball-milled at a speed of 100 r / min for 3 h and dried at 60°C for 1 h to obtain a functional filler.

[0053] Comparative Example 9 Comparative Example 9 is the same as Example 1, except that the composite filler does not contain silicon dioxide, as follows: Wherein, the functional filler in step S3 is prepared by the following method: (1) Mixing natural gum (composed of gum arabic and gum balsam pear mixed in a mass ratio of 5:1) with water in a mass ratio of natural gum, water and sodium hydroxide of 10:50:1, adding sodium hydroxide, stirring and mixing at a speed of 600 r / min for 10 minutes, and obtaining a natural gum solution; (2) According to the mass ratio of composite filler, lauryl amidopropyl betaine, polyethylene glycol and water being 6:1:2:50, a composite filler (composed of niobium nitride and calcium carbonate mixed in a mass ratio of 6:2) is added to lauryl amidopropyl betaine, polyethylene glycol and water, and the mixture is stirred and mixed at a speed of 600 r / min for 10 min to obtain a modified filler; (3) The modified filler was added to the natural gum solution at a mass ratio of 10:50, and the mixture was stirred at 400 r / min for 20 min. The mixture was then ball-milled at 100 r / min for 3 h, and dried at 60 °C for 1 h to obtain the functional filler.

[0054] Comparative Example 10 Comparative Example 10 is the same as Example 1, except that the composite filler does not contain calcium carbonate, as follows: Wherein, the functional filler in step S3 is prepared by the following method: (1) Mixing natural gum (composed of gum arabic and gum balsam pear mixed in a mass ratio of 5:1) with water in a mass ratio of natural gum, water and sodium hydroxide of 10:50:1, adding sodium hydroxide, stirring and mixing at a speed of 600 r / min for 10 minutes, and obtaining a natural gum solution; (2) According to the mass ratio of composite filler, lauryl amidopropyl betaine, polyethylene glycol and water being 6:1:2:50, a composite filler (composed of niobium nitride and silicon dioxide mixed in a mass ratio of 6:1) is added to lauryl amidopropyl betaine, polyethylene glycol and water, and the mixture is stirred and mixed at a speed of 600 r / min for 10 min to obtain a modified filler; (3) The modified filler was added to the natural gum solution at a mass ratio of 10:50, and the mixture was stirred at 400 r / min for 20 min. The mixture was then ball-milled at 100 r / min for 3 h, and dried at 60 °C for 1 h to obtain the functional filler.

[0055] Comparative Example 11 Comparative Example 11 is the same as Example 1, except that the composite filler is not modified, as follows: Wherein, the functional filler in step S3 is prepared by the following method: (1) Mixing natural gum (composed of gum arabic and gum balsam pear mixed in a mass ratio of 5:1) with water in a mass ratio of natural gum, water and sodium hydroxide of 10:50:1, adding sodium hydroxide, stirring and mixing at a speed of 600 r / min for 10 minutes, and obtaining a natural gum solution; (2) The composite filler (composed of niobium nitride, silicon dioxide, and calcium carbonate mixed in a mass ratio of 6:1:2) was added to the natural gum solution at a mass ratio of 10:50, and the mixture was stirred at 400 r / min for 20 min, then ball-milled at 100 r / min for 3 h, and dried at 60°C for 1 h to obtain the functional filler.

[0056] 1. Performance Testing 1. Piezoelectric performance test The surfaces of the composite high-temperature piezoelectric ceramic materials prepared in Examples 1-5 and Comparative Examples 1-11 of the present application were polished and cleaned, and after being coated with silver paste, the temperature was raised to 700°C and sintered for 10 minutes. The samples were polarized in a silicone oil bath at 100°C and a 10 kV / cm DC electric field for 30 minutes, and placed for 24 hours to obtain the samples. The piezoelectric properties of the samples were tested, and the test results are shown in Table 1.

[0057] 2. Mechanical properties test According to GB / T 23806-2009, the fracture toughness of the composite high temperature piezoelectric ceramic materials prepared in Examples 1-5 and Comparative Examples 1-11 was measured. The test results are shown in Table 1.

[0058] According to GB / T 4741-1999, the flexural strength of the composite high temperature piezoelectric ceramic materials prepared in Examples 1-5 and Comparative Examples 1-11 was measured. The test results are shown in Table 1.

[0059] Table 1

[0060] According to Table 1, the piezoelectric properties and mechanical properties of the composite high-temperature piezoelectric ceramic materials prepared in Examples 1-5 of the present application are significantly better than those of the composite high-temperature piezoelectric ceramic materials prepared in Comparative Examples 1-11, indicating that the composite high-valent ion components, the natural gum components, the functional filler components, and the preparation process and parameter limitations will significantly improve the piezoelectric activity and toughness of the piezoelectric ceramic materials. The composite high-temperature piezoelectric ceramic materials prepared in the present application not only have a high Curie temperature, but also have excellent piezoelectric and mechanical properties, and are environmentally friendly.

[0061] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A composite high temperature piezoelectric ceramic material, characterized in that: Its chemical formula is as follows: Bi 0.5-x [Mn 0.25 Sn 0.5 Pr 0.25 ] x Na 0.5 TiO3+a%WO3+b%ZnSO4; where x=0.1-0.3, a=1-3, b=0.4-0.6, WO3 accounts for Bi 0.5-x [Mn 0.25 Sn 0.5 Pr 0.25 ] x Na 0.5 TiO3 accounts for 1%-3% of the total molar amount, ZnSO4 accounts for Bi 0.5-x [Mn 0.25 Sn 0.5 Pr 0.25 ] x Na 0.5 0.4%-0.6% of the total molar amount of TiO3.

2. The method for preparing a composite high temperature piezoelectric ceramic material according to claim 1, characterized in that: The specific steps include: S1. According to the chemical formula, weigh Bi2O3 powder, MnO2 powder, SnO2 powder, Pr6O 11 powder, Na2CO3 powder, TiO2 powder, WO3 powder and ZnSO4 powder; S2, Bi2O3 powder, MnO2 powder, SnO2 powder, Pr6O 11 The powder, Na2CO3 powder, TiO2 powder and ethanol solution are mixed, ball-milled and dried, and then pre-calcined at 850-870°C for 3-5h to obtain a powder; S3, adding WO3 powder, ZnSO4 powder and functional filler to the powder, drying after ball milling, adding auxiliary agent for granulation, sieving and molding to obtain a ceramic body; S4. Debinding the ceramic body at 600-800° C., and then sintering at 1000-1200° C. for 2-4 hours to obtain a composite high-temperature piezoelectric ceramic material.

3. The method for preparing the composite high temperature piezoelectric ceramic material according to claim 2, characterized in that: The amount of ethanol solution added in step S2 is 10-14 times the mass of Bi2O3 powder.

4. The method for preparing a composite high-temperature piezoelectric ceramic material according to claim 2, characterized in that: The amount of the functional filler added in step S3 is 4%-8% of the mass of the powder.

5. The method for preparing the composite high temperature piezoelectric ceramic material according to claim 2, characterized in that: The functional filler in step S3 is prepared by the following method: (1) mixing natural gum with water, adding sodium hydroxide, and stirring to obtain a natural gum solution; (2) adding lauryl amidopropyl betaine, polyethylene glycol and water to the composite filler, stirring and mixing to obtain a modified filler; (3) Adding the modified filler into the natural gum solution, stirring and mixing, ball milling, and drying to obtain the functional filler.

6. The method for preparing the composite high temperature piezoelectric ceramic material according to claim 5, characterized in that: The natural gum in step (1) is at least one of gum arabic, peach gum and balsam pear gum.

7. The method for preparing the composite high temperature piezoelectric ceramic material according to claim 5, characterized in that: In the step (1), the mass ratio of natural gum, water and sodium hydroxide is 10-12:50:1-3.

8. The method for preparing a composite high-temperature piezoelectric ceramic material according to claim 5, characterized in that: In the step (2), the composite filler is composed of niobium nitride, silicon dioxide and calcium carbonate mixed in a mass ratio of 6-8:1-3:

2.

9. The method for preparing a composite high-temperature piezoelectric ceramic material according to claim 5, characterized in that: In the step (2), the mass ratio of the composite filler, lauryl amide propyl betaine, polyethylene glycol and water is 6-10:1-3:2-4:

50.

10. The method for preparing a composite high temperature piezoelectric ceramic material according to claim 2, characterized in that: In step S2, the ball milling speed is 240-260 r / min, the ball milling time is 24-36 h, and the drying temperature is 70-90° C.; in step S3, the ball milling speed is 200-220 r / min, the ball milling time is 18-30 h, and the drying temperature is 80-100° C.

Citation Information

Patent Citations

  • Potassium-sodium niobate and sodium lithium bismuth titanate-system lead-free piezoelectric ceramic composition

    CN102234195A

  • Wide-temperature-range sodium bismuth titanate-based leadless piezoelectric ceramic and preparation method thereof

    CN117886602A

  • BNT-based leadless piezoelectric ceramic and preparation method thereof

    CN119263819A

  • Bismuth sodium lithium titanate barium titanate strontium titanate calcium titanate based lead-free piezoelectric ceramics

    CN1541978A

  • Bismuth sodium titanate barium titanate strontium titanate calcium titanate based lead-free piezoelectric ceramics

    CN1541979A